Oxidative Dysregulation in Early Life Stress and Posttraumatic Stress Disorder: A Comprehensive Review - Evangelos Karanikas; Nikolaos P. Daskalakis; Agorastos Agorastos (Brain Sciences, 2021)
Traumatic stress may chronically affect master homeostatic systems at the crossroads of peripheral and central susceptibility pathways and lead to the biological embedment of trauma-related allostatic trajectories through neurobiological alterations even decades later. Lately, there has been an exponential knowledge growth concerning the effect of traumatic stress on oxidative components and redox-state homeostasis. This extensive review encompasses a detailed description of the oxidative cascade components along with their physiological and pathophysiological functions and a systematic presentation of both preclinical and clinical, genetic and epigenetic human findings on trauma-related oxidative stress (OXS), followed by a substantial synthesis of the involved oxidative cascades into specific and functional, trauma-related pathways. The bulk of the evidence suggests an imbalance of pro-/anti-oxidative mechanisms under conditions of traumatic stress, respectively leading to a systemic oxidative dysregulation accompanied by toxic oxidation byproducts. Yet, there is substantial heterogeneity in findings probably relative to confounding, trauma-related parameters, as well as to the equivocal directionality of not only the involved oxidative mechanisms but other homeostatic ones. Accordingly, we also discuss the trauma-related OXS findings within the broader spectrum of systemic interactions with other major influencing systems, such as inflammation, the hypothalamic-pituitary-adrenal axis, and the circadian system. We intend to demonstrate the inherent complexity of all the systems involved, but also put forth associated caveats in the implementation and interpretation of OXS findings in trauma-related research and promote their comprehension within a broader context.